An EMG study on characteristics of premotor and motor components in an agility reaction time test on athletes - Zhang, J.; Chen, R.; Wu, Y.; Li, K.; Wang,D.; Liu,Y.; Li Y. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: How do athletes control their foot movement so they can react fast in sports? Which component of the process may be more sensitive to training? These questions related to athletes` agility performance have long been important to the field of sport sciences, but are still unclear. The present study used surface electromyography (EMG) on the tibialis anterior (TA) and gastrocnemius medial (GM) of both left and right to assess if there would be any different contributions between premotor time (PRT) and motor time (MT) to the overall reaction time (RT). Methods: Fifty-five right-footed male college athletes (M=20.62 years old; SD=1.01) were required to respond to a random visual stimulus using foot movement as fast as possible in four different directions (i.e., forward and backward in their left or right foot). Results: High correlation coefficients between PMT and RT in all four directions (ranging from 0.866 to 0.909) were revealed, but not between MT and RT (ranging from 0.131 to 0.336). Lateral and sagittal axes significantly interacted based on RT. The left forward direction was slowest among all directions. Conclusion: The process of decision making, not the preparation of execution, plays a significant role in fast and accurate reactive responses; the slowest RT in the forward direction of the left foot may be related to response programming. The corresponding training should be emphasized in order to improve athletes` agility performance.